Predictive Factors, 30-Day Clinical Outcomes, and Costs Associated with Cerebrospinal Fluid Leak in Pituitary Adenoma Resection - Parikh, Adish; Adapa, Arjun; Sullivan, Stephen E.; McKean, Erin L. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Cerebrospinal fluid (CSF) leak is a complication of endoscopic endonasal pituitary adenoma resection. Previous studies examining complications of pituitary adenoma resection have not examined associations of an exhaustive list of clinical and financial variables with CSF leak. We designed a retrospective analysis of 334 consecutive patients that underwent endoscopic endonasal pituitary adenoma resection at a single institution over 5 years, analyzing associations between CSF leak and demographic data, operative data, comorbidities, clinical complications and outcomes, costs, charges, and payments. Of the 20 preoperative variables studied, none were positively associated with CSF leak in between-groups comparison, although multivariate analysis revealed an association with a history of radiation to the skull base (odds ratio [OR], 8.67; 95% confidence interval [CI], 0.94–57.03; p < 0.05). CSF leak was associated with a significantly higher rate of postoperative diabetes insipidus (Δ = 33.4%, p = 0.040) and increased length of stay after operation in between-groups comparison. Multivariate analysis on postoperative variables revealed significant associations between CSF leak and intracerebral hemorrhage (OR, 17.44; 95% CI, 0.65–275.3; p < 0.05) and postoperative intracranial infection (OR, 28.73; 95% CI, 2.04–438.7; p < 0.05). Also, CSF leak was associated with significantly higher costs (Δ = $15,643, p < 0.05) and hospital charges (Δ = $46,026, p < 0.05). Operating room time, room and board, and supplies and implants were the strongest cost drivers. This study highlights the difficulty of utilizing preoperative variables to predict CSF leak, the clinical complications and outcomes of leak, and the financial subcategories that drive the costs, charges, and payments associated with this complication.
Keywords: endoscopic endonasal approach; pituitary adenoma; cerebrospinal fluid leak; CSF leak; costs; complications; pituitary surgery